The Impact of Coal Mining on Ant (Formicidae) Abundance in Rice Field Areas, East Merapi, Lahat Regency, South Sumatra - Teristiandi, Novin; Yuliana, Meta (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The impact of coal mining pollution on rice fields located near mining areas can affect the health of communities that consume the harvested rice. Ants can serve as bioindicators of environmental pollution. This study aims to investigate the diversity of ants in rice fields located near and far from coal mining areas. The results show differences in ant diversity between rice fields near and far from the coal mining site. Ant species found in the rice field near the mining area included Leptogenys chamela (44 individuals), Solenopsis invicta (4 individuals), and Camponotus texanus (8 individuals). In contrast, in the rice field farther from the mining area, seven species were found: Solenopsis invicta (5 individuals), Myopias emeryi (71 individuals), Tetraponera rufonigra (37 individuals), Paraponera clavata (7 individuals), Leptogenys chamela (5 individuals), Dolichoderus sp. (1 individual), and Camponotus texanus (13 individuals). Ant abundance was higher in the rice field located farther from the coal mining area compared to the one located nearby.